Secure Data Transfer in Personal Area Network - Kumar, Shiv; shrama, Shrawan kumar; kumar, Awanit (IJRDO -Journal of Computer Science Engineering, 2015)
Now a d’ays everyone using net in their home or in small office or we can say within a small area. The problem is transfer data from one node to other node in a room or in a hall with minimum costing and minimum maintenance. But we have to save energy also. There are several techniques or method to transfer data in a small premise like Wi-Fi, Bluetooth, Li-Fi and quantum physics. According to our requirement security means privacy, integrity, timeliness and non repudiation. While costing is most important for small organization also. Implementation and maintenance of Wi-Fi is more costly then Li-Fi. Li-Fi is more secure then Wi-Fi because data is transfer from one node to another is done using light. It is cost effective also because we have not to use additional light to light the room or office. Its maintenance is also very easy. So, we can say that LI-Fi is better than Wi-Fi in terms of costing, privacy and maintenance.